Mangrove forest in India Exploring ecosystem services - Mitra, Abhijit (Switzerland Springer, 2020)
This is the comprehensive science-based primer to highlight the unique ecosystem services provided by mangrove forests, and discuss how these services preserve the livelihoods of coastal populations